Breaking down barriers: encouraging participation of underserved groups in STEM for the future - Ana María Guevara-Roselló; Jostin Joel Retana-Ledezma (Tecnología en Marcha)
This article focuses on a project carried out by the IEEE Computer Society Student Chapter at the Costa Rica Institute of Technology. The project was aimed to encourage the participation of underprivileged groups in STEM (Science, Technology, Engineering, and Mathematics) careers through workshops and educational activities. It was conducted in four schools with low economic growth, with a focus on the participation of women in the activities. The project successfully brought STEM education closer to these groups, providing them with opportunities and tools to explore these areas. The results obtained during the workshops reflected increased interest and understanding among the students regarding STEM career options. The article highlights the importance of this project in the context of Latin American countries, where the growth of STEM careers has been slow due to prejudices and sociocultural problems. Topics addressed in the article include the objectives, significance, and results of the activity, the definition of underprivileged groups, the challenges these groups face in choosing STEM careers, as well as the associated statistics. The article also includes post-project observations from the perspective of students, teachers, and volunteers, providing a more comprehensive view of the impacts and challenges faced.